Retrospective Cohort Study: Predictors of Viral Load Suppression Time Among People Living with HIV - Irma Tiara Rizky; Najmah Najmah; Iche Andriany Liberty (Journal La Medihealtico, 2025)
Acquired Immunodeficiency Syndrome (AIDS) represents the advanced stage of HIV infection and remains a major global public health challenge. Viral load testing is the main predictor of disease progression and a key indicator of antiretroviral (ARV) therapy success. In South Sumatra Province, viral load testing coverage in 2024 reached only 49%, below the national target of 75% and the global target of 95%, hindering progress toward the Ending AIDS 2030 goal. This study aimed to estimate the time to viral load suppression and identify its predictors among people living with HIV (PLHIV), complementing previous studies in areas with lower HIV prevalence. Using a retrospective cohort design and secondary data from the HIV AIDS and STI Information System Application version 2.1 (SIHA 2.1), the study analyzed 1,002 respondents through descriptive statistics and Cox regression survival analysis (Stata 15). Among the participants, 85.63% achieved viral load suppression, while 14.37% did not. Factors significantly associated with viral load suppression time included age (p = 0.016; HR 1.18; 95% CI 1.03–1.35), occupational status (p < 0.001; HR 1.63; 95% CI 1.34–1.99), ARV adherence (p = 0.007; HR 1.22; 95% CI 1.05–1.42), tuberculosis (TB) co-infection (p = 0.003; HR 1.31; 95% CI 1.09–1.57), and loss to follow-up history (p = 0.003; HR 1.41; 95% CI 1.12–1.75), after adjustment for sex and clinical stage. These findings underscore that age, employment, treatment adherence, TB co-infection, and LTFU history are key determinants of viral load suppression, emphasizing the need to strengthen treatment adherence programs to achieve the 95-95-95 targets and End AIDS 2030.